The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.cirp.2019.04.119
|View full text |Cite
|
Sign up to set email alerts
|

High surface quality micro machining of monocrystalline diamond by picosecond pulsed laser

Abstract: In micro machining of monocrystalline diamond by pulsed laser, unique processing characteristics appeared only under a few ten picosecond pulse duration and a certain overlap rate of laser shot. Cracks mostly propagate in parallel direction to top surface of workpiece, although the laser beam axis is perpendicular to the surface. This processed area can keep diamond structure, and its surface roughness is smaller than Ra = 0.2 µm. New laser micro machining method to keep diamond structure and small surface rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Monocrystalline diamonds were studied for micro-machining using a picosecond pulsed laser. 15 The results revealed that the cracks propagated in a direction parallel to the top surface of the workpiece. The researchers suggested a method that can be utilized for low-cost polishing of diamond surfaces using laser micro-machining.…”
Section: Introductionmentioning
confidence: 94%
“…Monocrystalline diamonds were studied for micro-machining using a picosecond pulsed laser. 15 The results revealed that the cracks propagated in a direction parallel to the top surface of the workpiece. The researchers suggested a method that can be utilized for low-cost polishing of diamond surfaces using laser micro-machining.…”
Section: Introductionmentioning
confidence: 94%
“…Under the action of femtosecond pulses, graphitization occurred layer by layer on the surface. Okamoto et al [21] studied the machining of monocrystalline diamond by picosecond laser (λ=1064nm, τ=12.5ps). acquiring the surface roughness less than 0.2μm.…”
Section: Progress Of Laser Polishingmentioning
confidence: 99%
“…Laser polishing of diamond has been extensively studied by a variety of laser sources spanning from continuous to pulsed lasers with wide wavelengths ranging from infrared (IR) to ultraviolet (UV). [34,35] At the normal incidence, the minimum average roughness R a is 0.2 µm. [34,36] It is found that the laser incidence angle is a key factor which significantly affects the surface roughness.…”
mentioning
confidence: 99%
“…[34,35] At the normal incidence, the minimum average roughness R a is 0.2 µm. [34,36] It is found that the laser incidence angle is a key factor which significantly affects the surface roughness. An average roughness R a down to 0.15 µm over a scan length of 0.5 mm was achieved at an incidence angle of 77° with respect to the diamond surface normal.…”
mentioning
confidence: 99%